2008
DOI: 10.1007/s11626-008-9120-2
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid prevents apoptotic cell death induced by trans10, cis12 isomer of conjugated linoleic acid via p38 MAP kinase dependent pathway

Abstract: Our previous study indicated that oleic acid prevented apoptotic cell death induced by trans10, cis12 (t10, c12)-conjugated linoleic acid in rat hepatoma dRLh-84 cells. The intracellular mechanism of action oleic acid is still unknown. Here, we showed that p38 mitogen-activated protein kinase (MAPK) inhibition using its specific inhibitor SB203580 cancelled the ameliorative effect of oleic acid on the cytotoxicity of t10, c12-conjugated linoleic acid. In addition, SubG1 cell population analysis showed that p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(15 reference statements)
2
8
0
Order By: Relevance
“…The effect of TOFN on TJ disruption and p38 activation is most likely due to the oleic acid coated on TOFN because oleic acid has been reported to decrease TER and the barrier function, disrupt cell–cell contacts as well as activate the p38 MAPK. ( 21,22 ) Taken together, we propose that HTOFN and TOFN‐induced TJ disruption is mediated through the activation of p38 and stress‐related signaling pathways.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of TOFN on TJ disruption and p38 activation is most likely due to the oleic acid coated on TOFN because oleic acid has been reported to decrease TER and the barrier function, disrupt cell–cell contacts as well as activate the p38 MAPK. ( 21,22 ) Taken together, we propose that HTOFN and TOFN‐induced TJ disruption is mediated through the activation of p38 and stress‐related signaling pathways.…”
Section: Discussionmentioning
confidence: 81%
“…Arachidonic acid activates members of the mitogen-activated protein kinase superfamily in rabbit proximal tubule cells 4 , hepatocytes 50 , and human brain endothelial cells (HBECs) 51 . The MUFA oleic acid has been shown to activate p38-MAPK in hepatocytes 52 and in rat hepatoma dRLh-84 cells 53 . In vascular endothelial cells, LA activates p38-MAPK within 10 min of treatment 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Magdalon et al (2012) revealed that oral administration of OA modulated the production of inflammatory mediators including IL-1β, IL-6, and CINC-2αβ in rat macrophages. Several groups have demonstrated that OA suppressed the inflammation by down-regulating COX-2 expression and preventing p38 activation in cell types such as cardiac myocytes, and mouse hepatocytes, among others (Cardoso et al, 2011;Liu et al, 2007;Miller et al, 2005;Yamasaki et al, 2008). OA pretreatment displayed better protection of neuronal cells against palmitic acid-or insulin resistance-associated damage than those of docosahexaenoic acid (DHA) or linoleic acid (Kwon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%